2021
DOI: 10.1002/ajmg.a.62098
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic phenotypes associated with biallelic loss‐of‐function PCDH12 variants

Abstract: Individuals carrying biallelic loss‐of‐function mutations in PCDH12 have been reported with three different conditions: the diencephalic–mesencephalic junction dysplasia syndrome 1 (DMJDS1), a disorder characterized by global developmental delay, microcephaly, dystonia, and a midbrain malformation at the diencephalic–mesencephalic junction; cerebral palsy combined with a neurodevelopmental disorder; and cerebellar ataxia with retinopathy. We report an additional patient carrying a homozygous PCDH12 frameshift,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…After initial screening, 134 articles were included for data extraction and analysis based on full-text review. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146]…”
Section: Resultsmentioning
confidence: 99%
“…After initial screening, 134 articles were included for data extraction and analysis based on full-text review. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146]…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that PCDH12 variants should be considered in the differential diagnosis for congenital microcephaly and neurodevelopmental delay associated with intrauterine infections [12]. The identified PCDH12 variants are displayed on protein domains in Figure 4 [10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…On molecular grounds, DMJD is currently divided into two types: type 1 (DMJD1) due to biallelic PCDH12 pathogenic variants and type 2 (DMJD2) due to biallelic GSX2 pathogenic variants. To date, 19 affected families with PCDH12-related DMJD (DMJD type 1) have been reported, while only 2 affected families with GSX2-related DMJD (type 2) have been reported [9][10][11][12][13][14][15][16]. PCDH12 encodes a cell adhesion molecule termed protocadherin-12 that is a member of the nonclustered protocadherin family of calcium-dependent cell adhesion proteins.…”
Section: Introductionmentioning
confidence: 99%
“…PCDH12 loss of function results in a wide neurological phenotypic spectrum including cerebral palsy, microcephaly, intellectual disability, speech impairment, seizures, and psychomotor delays. Brain imaging further revealed brainstem malformations, white matter abnormalities, cerebellar ataxia, and brain calcifications (Aran et al, 2016;Fazeli et al, 2022;Guemez-Gamboa et al, 2018;Mattioli et al, 2021;Suzuki-Muromoto et al, 2018;Vineeth et al, 2019). Despite such severe neurodevelopmental abnormalities resulting from PCDH12 deficiency, little is known about its function in brain development and disease.…”
Section: Introductionmentioning
confidence: 99%